STRATEGI COMPETITIVE ADVANTAGE UNTUK MEMBANGUN CITY BRANDING KOTA BATU SEBAGAI KOTA WISATA - Miladiyah, Uyunur Rochmawati; Slamet, Slamet (IQTISHODUNA, 2014)
Globalization led to tough competition among cities around the world to win the competition toattract visitors and increase investment. Therefore, not only the company, the cities are also struggling tocreate uniqueness to gain an advantage in competition. It is very important to communicate the competitiveadvantages owned by these cities to the public and all parties to ensure the achievement of objectives. Citybranding is a method used to re-brand the city as identification which is expected to reflect the advantages aswell as its uniqueness. Therefore, in 2013 Shining Batu was introduced as a city brand wich expected to bereflect the competitive advantage of Batu City. The purpose of this study is to reveal aspects of the competitiveadvantages Batu City; strategies that are used in communicating it; as well as how big the impact of thecommunication strategy for the visitors Batu City. The paradigm of this research is qualitatively by case studydesign. Data were obtained by interview and documentation. The results showed that the Batu City has threeinterrelated aspects superior to one another that supports the creation of competitive advantages: geographicand agricultural sectors are packed in the development of the tourism sector. At the same time, the governmentdeveloped the program as a means of communicating Shining Batu and reflects the benefits of the city to thepublic. Shining Batu communicated through various forms of promotion that utilizes a wide variety ofcommunication tools; a variety of Tour Package; and held aa variety of routine and incidental events.Questionnaire showed that aim to dominate the number of respondents traveled, which consists of a visitor,where recreational tourist attractions types over a favorite choice than any natural attractions. Hotel is a topchoice for a place to stay. Most visitors make a visit to Batu City more than once.